2020
DOI: 10.1093/nsr/nwaa188
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ancestral phenotypes and evolutionary development of the mammalian middle ear based on Early Cretaceous Jehol mammals

Abstract: We report a new Cretaceous multituberculate mammal with 3D auditory bones preserved. Along with other fossil and extant mammals, the unequivocal auditory bones display features potentially representing ancestral phenotypes of the mammalian middle ear. These phenotypes show that the ectotympanic and the malleus-incus complex changed notably during their retreating from the dentary at various evolutionary stages and suggest convergent evolution of some features to extant mammals. In contrast, the incudomalleolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 44 publications
4
18
1
Order By: Relevance
“…The authors hypothesized that a middle ear with a monotreme-like incus and malleus and incudomallear articulation was primitive for mammals, which challenges the convention that the monotreme middle ear is specialized 3 or autapomorphic 4 in mammals. We raise concerns about terminology and identification of the incus presented by Wang et al and show that their analysis does not support their hypothesis; instead, it supports the one by Mao et al 5,6 .…”
contrasting
confidence: 73%
See 4 more Smart Citations
“…The authors hypothesized that a middle ear with a monotreme-like incus and malleus and incudomallear articulation was primitive for mammals, which challenges the convention that the monotreme middle ear is specialized 3 or autapomorphic 4 in mammals. We raise concerns about terminology and identification of the incus presented by Wang et al and show that their analysis does not support their hypothesis; instead, it supports the one by Mao et al 5,6 .…”
contrasting
confidence: 73%
“…Contrary to the existing hypothesis that the braced hinge joint (=partial overlapping joint, POJ; Fig. 1b, i, j) is potentially primitive for mammals 6 , Wang et al concluded that optimization of five incudomallear characters in their phylogeny (Fig. 2a) ‘supports the overlapping joint as primitive for Mammalia.…”
mentioning
confidence: 83%
See 3 more Smart Citations